Digital democracy and brokerage dynamics in regional head elections in Indonesia - Anyualatha - Haridison (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The progress of the digitalization era in democracy has led to changes in the current political contestation, especially the way candidates approach voters. This study explores broker schemes in the digital world regarding how candidates use social media to build a broker network. This study used qualitative research, by observing social media and interviewing several key informants. This study finds that in the era of digital democracy, candidates use social media to develop digital brokers, but as a pre-elaboration and intensively introduce the candidate's real work to voters. Some candidates believe that conventional brokers are still final in knowing and binding broker loyalty, but winning candidates experiment with digital brokers. On the other hand, digital democracy has provided space for candidates to focus on brokers on social media to code the brokers who will be targeted or nominated to become structured conventional brokers. This study expands the study of brokers in electoral political studies, especially insights related to digital brokerage schemes and adds focus to the study of regional elections in Indonesia. This study concludes that digital brokers are a strategy for expanding digital voter networks and persuading candidates' work to voters on social media in the long term.